Komplikasi letal pada bayi sangat prematur dengan sifilis kongenital - Gozali, Ferry Suganda; Liman, Claudia Natasha; Suryaningsih, Putu Siska (PT Kalbe Farma Tbk., 2024)
Introduction: Congenital syphilis is a multi-organ infection caused by Treponema pallidum and transmitted from mother to fetus through uteroplacental circulation. Congenital syphilis is one of the main contributors to neonatal deaths in the United States. Case: A male infant was born by cesarean delivery from a G1P0 mother at 28 weeks of gestational age because of premature rupture of the membrane and anhydramnion. The mother had an untreated latent syphilis infection. The birthweight was 1,400 grams, the head circumference was 25 cm, and the body length was 35 cm. His APGAR score was 3-3-5 with severe asphyxia and respiratory distress syndrome. Multiple abnormalities were found, and the VDRL titre was 1/128. Cardiac-pulmonary resuscitation started immediately with 0.15 mg epinephrine through an intraendotracheal tube and continued with 0.02 mg epinephrine through intravenous access every 3 minutes. The baby was declared dead after 30 minutes of resuscitation. Conclusion: Congenital syphilis can cause lethal complications due to untreated latent syphilis suffered by his mother. The mother should undergo antenatal screening to prevent congenital syphilis.